(untitled) (Research, Society and Development, 2021)
Digital Mathematical Performances (PMDs) can be understood initially as a perspective of Mathematical Education that integrates the performing arts and digital technologies with Mathematical Education. Taking into account the themes that involve PMDs - digital arts and technologies - and taking inspiration from academic productions on the subject, this article aims to present, based on one of the themes of PMDs: digital technologies - a trajectory that starts with the entry of computer technology in Brazilian schools until the most current projects that involve discussions of digital technologies with arts and Mathematics Education, through the PMDs. Based on a qualitative research methodology, with the particular study of the event Brazilian Meeting of Graduate Students in Mathematics Education to unveil the current research projects on digital technologies, we divided this article into two sections, namely: the first one is intended to address some government actions to encourage digital technologies in Brazilian public schools and the second describes how far we have come in terms of research projects on digital technologies in Mathematics Education, emphasizing, for this, projects linked to LDCs. It is concluded, among other factors, that the LDCs present themselves as a powerful proposal for teaching and learning in mathematics since, in addition to articulating digital technologies to mathematics education, it is concerned with incorporating the (performing) arts in this process, as well as demystifying stereotypes of mathematics and of those who practice it, giving protagonism to students in productions from different research projects.